Procedural and short-term safety of bronchial thermoplasty in clinical practice: evidence from a national registry and Hospital Episode Statistics. (14th September 2017) - Burn, Julie; Sims, Andrew J.; Keltie, Kim; Patrick, Hannah; Welham, Sally A.; Heaney, Liam G.; Niven, Robert M.
ABSTRACT: Objective: Bronchial thermoplasty (BT) is a novel treatment for severe asthma. Its mode of action and ideal target patient group remain poorly defined, though clinical trials provided some evidence on efficacy and safety. This study presents procedural and short-term safety evidence from routine UK clinical practice. Methods: Patient characteristics and safety outcomes (procedural complications, 30-day readmission and accident and emergency (A&E) attendance, length of stay) were assessed using two independent data sources, the British Thoracic Society UK Difficult Asthma Registry (DAR) and Hospital Episodes Statistics (HES) database. A matched cohort (with records in both) was used to estimate safety outcome event rates and compare them with clinical trials. Results: Between June 2011 and January 2015, 215 procedure records (83 patients; 68 treated in England) were available from DAR and 203 (85 patients) from HES. 152 procedures matched (59 patients; 6 centres), and of these, 11.2% reported a procedural complication, 11.8% resulted in emergency respiratory readmission, 0.7% in respiratory A&E attendance within 30 days (20.4% had at least one event) and 46.1% involved a post-procedure stay. Compared with published clinical trials which found lower hospitalisation rates, BT patients in routine clinical practice were, on average, older, had worse baseline lung function and asthma quality of life. Conclusions: A higher proportion of patients experienced adverse events compared with clinical trials. The greater severity of disease amongst patients treated in clinical practice may explain the observed rate of post-procedural stay and readmission. Study of long-term safety and efficacy requires continuing data collection.